Prevalence, epidemiology and molecular studies of Tomato chlorosis virus (ToCV) in South Africa. - Vaneson Moodley; Augustine Gubba; Paramu L Mafongoya (PLoS ONE, 2019)
Criniviruses accumulate in the phloem tissue and damage crops by reducing chlorophyll which is essential for plant growth and development. Tomato chlorosis crinivirus (ToCV) is vectored by several whitefly species that damage tomato crops throughout the world. In South Africa, ToCV is a poorly studied pathogen of global economic importance. Therefore, a national survey was initiated to investigate the occurrence and distribution of criniviruses infecting tomato crops in South Africa. Whitefly infested tomato crops exhibiting interveinal leaf chlorosis and chlorotic flecking symptoms were assayed for crinivirus infections using a multiplex reverse transcription polymerase reaction (RT-PCR) approach to assess for the presence of crinivirus species that are known to infect solanaceous hosts. Next-generation sequencing (NGS) was used to generate the complete genome of ToCV from South Africa. Results from the survey indicated that ToCV is presently the only crinivirus species infecting tomatoes in South Africa. Blast analysis showed that the RNA-1 segment of ToCV from South Africa (ToCR1-186) matched 99% to Spanish isolates. On the other hand, the RNA-2 (ToCR2-186) segment matched 98% to a South Korean isolate and three Spanish isolates. Although recombination events were not detected, phylogenetic studies showed inconsistencies in the grouping of RNA-1 and RNA-2 segments for some of the ToCV isolates analyzed in this study. Therefore, we suggest the possibility of intraspecific reassortment. This is the first comprehensive study and full genome sequence of ToCV from South Africa. The information generated from this study is intended to raise awareness of ToCV infections on tomato crops in South Africa.